2015
DOI: 10.1111/joor.12368
|View full text |Cite
|
Sign up to set email alerts
|

Locators versus magnetic attachment effect on peri‐implant tissue health of immediate loaded two implants retaining a mandibular overdenture: a 1‐year randomised trial

Abstract: This study aimed to evaluate peri-implant tissue health of immediate loaded two implants retaining a mandibular overdenture with either magnetic or locator attachment. Thirty two completely edentulous patients (20 males/12 females) were randomly assigned into two groups. Each patient received two implants in the canine area of the mandible using flapless surgical technique. Mandibular overdentures were immediately connected to the implants with either magnetic (group I, GI) or locator (group II, GII) attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 36 publications
5
71
0
Order By: Relevance
“…The clinical findings reported in the present study, with a success rate of 83.3% for NDI connected to locking taper stud abutments as MO retainers, demonstrate a stable clinical behavior after the osseointegration period. However, some studies showed a significant increase in the peri-implant health indices over time 16,35,36. The evaluations of the PI, GI, and calculus index in our study indicate that higher values for these indices occur during osseointegration.…”
mentioning
confidence: 38%
See 2 more Smart Citations
“…The clinical findings reported in the present study, with a success rate of 83.3% for NDI connected to locking taper stud abutments as MO retainers, demonstrate a stable clinical behavior after the osseointegration period. However, some studies showed a significant increase in the peri-implant health indices over time 16,35,36. The evaluations of the PI, GI, and calculus index in our study indicate that higher values for these indices occur during osseointegration.…”
mentioning
confidence: 38%
“…Despite the fact that it is known that the attachment system based on a stud abutment has greater retention and stability than ball or magnet type systems, the results from Elsyad et al36 showed that a group rehabilitated with locator type stud abutments experienced 0.31 mm more vertical MBL than a group using magnetic abutments after 1 year. Despite the fact that it is known that the attachment system based on a stud abutment has greater retention and stability than ball or magnet type systems, the results from Elsyad et al36 showed that a group rehabilitated with locator type stud abutments experienced 0.31 mm more vertical MBL than a group using magnetic abutments after 1 year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the repair and replacement of these attachments is simple and easy (7,8). Furthermore, Locator attachments are associated with favorable clinical and radiographic peri-implant outcomes (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…There is an absence of contrasted, and more long-term, evidence on the reduction or non-overloading of implant angulation, following the All on four protocols [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%